Path Analysis on the Biopsychosocial Determinants of Infertility among Reproductive Aged Women in Surakarta, Central Java - Zauma, Luthfia; Budhiastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background:  Infertility is a multidimensional problem. This problem occurs not only because of health problems related to anatomic factors such as problems in the fallopian tubes, ovaries, and endometrium, but also there are more factors such as physiological, genetic, and environmental factors. The purpose of this study was to analyze the factors that influence the incidence of infertility in women.Subjects and Method: A case control study was conducted at the Gynecology Obstetrics Polyclinic and Sekar Fertility Clinic, Dr. Moewardi hospital, Surakarta, Central Java, from October to November 2019. A sample of 200 women reproductive age was selected by fixed disease sampling. The dependent variable was infertility. The independent variables were age, body mass index (BMI), physical activity, endometriosis, family history, exposure to cigarette smoke, and stress. The data were obtained from medical record and questionnaire. The data were analyzed by path analysis run on Stata 13.Results: Infertility in women was directly increased with age 35 years (b= 1.20; 95% CI= 0.18 to 2.22; p= 0.021), BMI <18 or ≥25 (b= 2.93; 95% CI= 1.95 to 3.91; p<0.001), high physical activity (b= 1.30; 95% CI= 0.28 to 2.33; p= 0.013), endometriosis (b= 1.17; 95% CI= 0.20 to 2.13; p= 0.018), exposure to cigarette smoke (b= 1.19; 95% CI= 0.20 to 2.23; p= 0.023), and severe stress (b= 1.18; 95% CI= 0.27 to 2.08; p= 0.011). Infertility in women was indirectly increased with age, physical activity, and family history of infertile.Conclusion: Infertility in women is directly increased with age 35 years, BMI <18 or ≥25, high physical activity, endometriosis, exposure to cigarette smoke, and severe stress. Infertility in women is indirectly increased with age, physical activity, and family history of infertile.Keywords: female infertility, risk factors, path analysisCorrespondence: Luthfia Zauma. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia, 57126. Email:el.chizauma@gmail.com. Mobile: 0813379 77377.Journal of Maternal and Child Health (2020), 5(2): 173-181https://doi.org/10.26911/thejmch.2020.05.02.07